The potential roles of sponges in integrated mariculture. (26th October 2020) - Gökalp, Mert; Mes, Daan; Nederlof, Marit; Zhao, Hongwei; Merijn de Goeij, Jasper; Osinga, Ronald
Abstract: This mini‐review evaluates the use of marine sponges in integrated culture systems, two decades after the idea was first proposed. It was predicted that the concept would provide a double benefit: sponges would grow faster under higher organic loadings, and filtration by sponges would improve water quality. It is promising that the growth of some commercially interesting sponges is indeed faster in organically enriched areas. The applicability of sponges as filters for undesired microorganisms has been confirmed in laboratory studies. However, upscaled farming studies need to be done to demonstrate the value of sponges for in situ bioremediation of sewage discharge or waste produced by fish cages. In addition, a new idea is presented – the use of sponges as an engine to convert dissolved organic matter (DOM) into particulate organic matter (POM) that can be consumed by deposit feeders through a chain of processes termed the sponge loop. A theoretical design of an integrated culture with seaweeds ( Gracilaria sp.), sponges ( Halisarca caerulea ) and sea cucumbers ( Apostichopus japonica ) shows that 37% of the part of the primary production that is excreted by the seaweeds as DOM can be directly recovered in sponge biomass and a subsequent 12% in sea cucumber biomass after mediation (conversion of DOM to POM) by sponges. Hence, the total recovery of DOM into (sponge and sea cucumber) biomass within this IMTA is 49%.